2012
DOI: 10.1002/cssc.201200274
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Ionic Liquid Modified Mesoporous Carbon: A Tailor‐made Nanostructure Biosensing Platform

Abstract: A novel nanocomposite based on ordered graphitized mesoporous carbon (GMC) and amino acid ionic liquids (AAIL) is obtained through controlled surface modification of GMC with hydrophilic AAILs (1-ethyl-3-methylimidazolium alanine, EMIM[Ala]), which is used as a platform for a tyrosinase biosensor to detect phenol. The GMC-AAIL nanocomposite possesses a better biocompatibility and improved aqueous-phase dispersion than hydrophobic GMC alone, owing to the introduction of hydrophilic and biocompatible AAILs. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 165 publications
(165 reference statements)
0
16
0
1
Order By: Relevance
“…The effective immobilization of enzyme molecules is one of the key factors in developing high performance enzyme biosensor. To seek for better immobilization matrixes, a variety of materials including graphene (Wang et al, 2010), mesoporous carbon (Wu et al, 2012b), metal nanoparticle (Saei et al, 2013), carbon nanotube (Vashist et al, 2011), metal oxide (Lu et al, 2008) and conducting polymer (Zhai et al, 2013) have already been explored to modify the electrodes for improving the loading amount as well as the bioactivity of the enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The effective immobilization of enzyme molecules is one of the key factors in developing high performance enzyme biosensor. To seek for better immobilization matrixes, a variety of materials including graphene (Wang et al, 2010), mesoporous carbon (Wu et al, 2012b), metal nanoparticle (Saei et al, 2013), carbon nanotube (Vashist et al, 2011), metal oxide (Lu et al, 2008) and conducting polymer (Zhai et al, 2013) have already been explored to modify the electrodes for improving the loading amount as well as the bioactivity of the enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…As shown, GMC exhibits a highly ordered porous structure with a pore diameter of 10 nm, which is indicative of the formation of an ordered mesoporous structure. These spherical pores are interconnected by adjacent smaller windows, which could provide mass‐transfer channels for the enzyme‐catalyzed substrate and product 21. More importantly, the mesopores with a pore size of 10 nm could provide a favorable microenvironment to accommodate the Tyr molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study revealed that GMC with proper pore‐size matching for enzyme molecules could accommodate enzyme molecules into their mesopores thus to provide a protective microenvironment to prevent enzyme deactivation 16. 21 As for Co 3 O 4 , it has good hydrophilicity and biocompatibility 19. The combination of Co 3 O 4 with GMC resulted in the formation of a novel nanocomposite with improved hydrophilicity and biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations